Efficacy and Pharmacological Mechanism of Poria cocos-Based Formulas Combined With Chemotherapy for Ovarian Cancer: A Integrated Systems Pharmacology Study - Peng, Xinya; Jia, Congchao; Chi, Hao; Wang, Pengyu; Fu, Hu; Li, Yunyue; Wang, Qin (Frontiers in Pharmacology, 2022)
Previous studies have shown that Poria cocos-based formulas combined with chemotherapy can improve the quality of life of ovarian cancer patients. However, the results are still controversial. We systematically searched the literature from eight databases to evaluate the efficacy and safety of Poria cocos-based formulas in combination with paclitaxel-carboplatin in treating ovarian cancer (OC). Subsequently, network pharmacology, molecular docking and cell experiments were performed to further verify the underlying molecular mechanism. Thirteen randomized controlled trials, including 922 patients with OC, were enrolled in the study. The results indicated that Poria cocos-based compounds combined with paclitaxel-carboplatin significantly improved patients’ tumor response rate, traditional Chinese medicine syndrome score, Karnofsky Performance Scale, physical and social function, and reduced side effects of chemotherapy compared to the paclitaxel-carboplatin alone. According to the network pharmacological analysis, tumulosic acid were the most bioactive compounds of Poria cocos. BCL2L1 is highly expressed in OC and is associated with a worse prognosis which could become potential drug target. Functional enrichment analysis suggested that the anti-OC effect of Poria cocos may be related to PI3K-Akt signaling pathway. The molecular docking results indicated that tumulosic acid might inhibit OC by regulating BCL2L1. Vitro experiment confirmed tumulosic acid that induced cell apoptosis by modulating PI3K/Akt signaling and BCL2L1. Our study may provide a clinical basis and theoretical rationale for combining Poria cocos-based formulas with chemotherapy for OC. In addition, the integrated pharmacological strategy proposed in our study provides an excellent example for exploring the mechanism of complex formulas.